BRINCANDO NO LEITO: CRIANDO MÉTODOS E PERSPECTIVAS - Leonardo de Oliveira Barros; Patricia Alessandra Fukura de Abreu; Thays Mayara Alli de Andrade; Daiane da Silva Videira; Josiane Machado Ruiz (Colloquium Humanarum, 2016)
The hospital playroom aims to reduce the negative aspects of hospitalization of children and adolescents, allowing contact with the play, however, on-site observations indicated a large number of children who can not get around to the playroom. This research aimed to build a hospitalized child care protocol that needs to stay on bed rest. There were 56 children of both sexes, 0-17 years admitted to the pediatric ward of a regional hospital in the state of São Paulo. Data were collected from recreational activities, self-assessment of the mood at the beginning and end of care and registration script. It was found that the play has contributed significantly to improve the mood of children and adolescents and the data helped to design intervention strategies for brinquedistas in caring for children and adolescents bedridden.